THE EFFECT OF PICTURE SERIES ON THE STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT AT SMAN 7 KEDIRI - Yeri Febrian; Diani Nurhajati; Yunik Susanti (JURNAL KOULUTUS, 2024)
Writing must be taught to secondary school students when they study English at school. During teachingpractice at SMAN 7 Kediri, the researchers identified several problems when the students were taught towrite English texts. Most students had difficulty to develop ideas and make English sentences. Therefore,experimental research was carried out using picture series to teach writing narrative text. This researchaims at describing the development of students' writing skills before and after being taught using seriesof pictures by applying quantitative research methods. Data collection was carried out through pre-test and post-test writing on 34 eleventh grade students at SMAN 7 Kediri as the sample. Data wereanalyzed using the SPSS Statistics 26 tool. After being given treatment in learning using visual media inthe form of a series of images, students' ability to write narrative text showed improvement. The resultsof the t-test calculation show that there is a significant mean difference between the pre-test and post-test scores. The Sig (2-tailed) value of the comparison between pre-test and post-test is 0.000, whichis lower than 0.005, while the results obtained are significant if <0.005. So, it can be concluded thatthe to series of pictures is an effective medium for teaching writing, especially writing narrative texts.Therefore, it is recommended that English teachers use series of pictures as a teaching medium to teachwriting narrative texts